(3GdJfHjgGJ Ydi eG aj GdJHjGf ef GdJehjgGJs - (3eMeO Hf YejQI GdeNRheis; (3GdRedcGfj , ceGd GdOjf CHh GdecGQe YHO GdhGMO GdSeGcj, GdRedcGfj,J (B651 (3g` s
(3ChdgG (B:s
(3GHJOC Gdbhd ai GdOdGdI GdEaQGO s
(3BNQgG (B:s
(3GdPi eQ ef GdcdGe Ydi eGeVi ef GdcJGH ced GdQO HMeO Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B209s
Keywords: (3GdHdGZIs